Coherent transport in Y-junction graphene waveguide. (10th October 2018) - Mosallanejad, Vahid; Chiu, Kuei-Lin; Guo, Guo-Ping
Abstract: We performed a series of theoretical transport studies on Y-branch electron waveguides which are embedded in mid-size armchair graphene nanoribbons. Non-equilibrium Green's function with different approximations of tight-binding Hamiltonian has been employed. Using the first nearest hopping approximation, we observed very pronounced conductance quantization, the structure of which depends on geometrical design and shows a spacing of 4 e 2 / h, indicating the existence of valley degree of freedom. Moreover, by incorporating the third nearest approximation, we observed seminal plateaus deviated from multiples of 4 e 2 / h conductance, suggesting the lift of valley degeneracy. Finally, Quasi-one dimensional band structure calculations have been performed to study the availability of energy channels and the role of the major geometrical parameters on the transport.